Was America founded as a Christian nation? : a historical introduction - Fea, John. (Louisville, Ky. : Westminster John Knox Press, 2011)
Explores the question of whether America was founded as a Christian nation, discussing what it means to think historically, examining the history of the idea that the United States is a Christian nation, exploring the relationship between Christianity and the coming of the American Revolution, and investigating the specific religious beliefs of the founders.
Introduction: how to think historically -- Evangelical America, 1789-1865 -- Evangelicals, liberals, and Christian America, 1865-1925 -- Christian America in a modern age, 1925-1980 -- History for the faithful: the contemporary defenders of Christian America -- Were the British colonies Christian societies? -- Christianity and the coming of the American Revolution -- The Revolutionary pulpit -- Nature's God: is the Declaration of Independence a Christian document? -- Religion in the critical period -- A "Godless constitution"? -- Did George Washington pray at Valley Forge? -- John Adams: devout Unitarian -- Thomas Jefferson: follower of Jesus -- Benjamin Franklin: ambitious moralist -- What about Witherspoon? Three Orthodox founders.
Includes bibliographical references (p. 247-273) and index.
Keywords: Christianity and politics -- United States -- History; United States -- Church history